Dark-probe scanning near-field microscopy - Henrik Parsamyan; Torgom Yezekyan; Khachatur Nerkararyan; Sergey I Bozhevolnyi (New Journal of Physics, 2023)
Scanning near-field optical microscopy (SNOM) is a well-known powerful optical technique for visualization of surface nanostructures and fields far beyond the diffraction limit and thus indispensable in material- and nanoscience. While the SNOM resolution is theoretically unlimited, the SNOM performance is in practice constrained by the signal-to-background ratio, simply because of light scattering scaling down as the sixth power of a nanoparticle size and useful signals rapidly drowning in the background for very small objects. In modern instruments, this problem is usually ameliorated through advanced post-processing techniques. Here, we suggest using, instead or in parallel, a ‘dark’ SNOM probe designed to suppress the background light scattering, so that the scattering occurs only when the probe is very close to a nanoscopic object. We argue and demonstrate with simulations that the dark-probe SNOM imaging is much more sensitive to the presence of tiny nanoparticles or any other nanoscale features, allowing thereby for superior resolution and sensing capabilities that are invaluable for nano-optical characterization.